Exploring local consequences of two land-use alternatives for the supply of urban ecosystem services in Stockholm year 2050. (November 2016) - Kain, Jaan-Henrik; Larondelle, Neele; Haase, Dagmar; Kaczorowska, Anna
Highlights: Fine-grained mapping is required to explore links between land use and urban ES supply. Supply of urban ESs varies considerably within identical land-use classes. ES supply measures on neighborhood and building levels matter a great deal. Easily applicable indicators and methods are not available for urban planners. Detailed land-use and ES modeling should be used at early stages of planning and policy. Abstract: Ecosystem services (ESs) are gaining ground in urban policy as a key to attaining sustainable cities. However, strategic and land-use planners need operational and accessible tools to better understand the consequences of policy and planning measures. Based on a study of the City of Stockholm and its surrounding region, we argue that spatially explicit land-use mapping is a good base for modeling and visualizing the supply of urban ESs provided by different patterns of Service Providing Units. By adding more detailed characteristics of land use through the concept of Service Providing Elements (SPEs), and by assessing synergies and trade-offs between these attributes, implications for the supply of ESs at different scale levels could be identified and discussed. Detailed land-use mapping and ES modeling were applied to two future land-use alternatives. The supply of eight urban ESs was found to vary significantly between the two alternatives depending on the ratios of different SPEs, even within identical land-use classes. One of the land-use alternatives had significantly higher potential for food and energy provision, much higher air cooling and air quality regulation capacity especially in densely built areas, showed less surface sealing, and provided better conditions for mental recreation. The exception was supply of physical recreation opportunities, where the other land-use option had an advantage. These differences became more accentuated when we zoomed in on two local urban areas. Based on these findings, our main conclusion is that, in order to provide planning and policy-making with an adequate knowledge base, it is necessary to move beyond land-use classes, as defined by European data sets like Urban Atlas, and toward tools capable of capturing more detailed aspects of land use and its relations to the supply of urban ESs. This should be made a priority, especially in early stages of planning and policy formation, and also used to support development of urban by-laws, procurement arrangements, neighborhood and building certification, etc. The approaches used in the study can serve as a valid starting point for further development of such tools and methods compatible with planners' ordinary working modes. However, to make such progress possible, the ecosystem service research community needs to step up to the challenge of delivering locally specific and useful data on how urban land-use links to ES supply, including synergies and trade-offs between different ESs.